Hubungan Neutrophil Lymphocyte Ratio, Platelet Lymphocyte Ratio, dan Ferritin dengan Pemberian Remdesivir pada Pasien Covid-19 dengan Peningkatan Transaminase - Linda W. A. Rotty; Decky Andrea; Fujiyanto Fujiyanto; Harlinda Haroen; Pearla Lasut; Cecilia Hendratta; Agung Nugroho; Efata Polii (Universitas Sam Ratulangi, 2023)
Abstract: Remdesivir is used as the treatment for coronavirus disease 2019 (Covid-19). Moreover, its pharmacological effect has an impact on the improvement of inflammatory biomarkers. Neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), and ferritin are simple inflammation parameters that are widely available and can describe inflammation in Covid-19 patients. This cross-sectional study involved 52 Covid-19 patients at Prof. Dr. R. D. Kandou Hospital from March 2020 to March 2021. Blood tests were performed on the day before remdesivir administration and one week after administration. The results obtained a significant correlation between NLR and PLR with a value of r=0.641-0.670 (p<0.001) before and after administration of remdesivir. In all patients there was a decrease in ferritin with remdesivir administration (∆= -111.41). In conclusion, there are decreases in NLR, PLR and ferritin values ​​in Covid-19 patients with increased transaminase after being treated with remdesivir, especially living patients. Keywords: remdesivir; coronavirus disease 2019 (Covid-19); platelet lymphocyte ratio; neutrophil lymphocyte ratio; ferritin Abstrak: Remdesivir termasuk dalam tatalaksana coronavirus disease 2019 (Covid-19). Efek farmakologik remdesivir juga berdampak terhadap perbaikan biomarker inflamasi. Neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), dan feritin merupakan parameter inflamasi sederhana yang banyak tersedia dan dapat menggambarkan inflamasi pada pasien Covid-19. Studi potong lintang ini menelaah 52 pasien Covid-19 di RSUP Prof. Dr. R. D. Kandou sejak Maret 2020 hingga Maret 2021. Pemeriksaan darah diambil pada hari sebelum pemberian remdesivir dan satu minggu setelah pemberian. Hasil penelitian mendapatkan korelasi bermakna antara NLR dan PLR dengan nilai r=0,641-0,670 (p<0,001) baik sebelum dan setelah pemberian remdesivir. Pada keseluruhan pasien terdapat penurunan ferritin dengan pemberian remdesivir (∆=-111,41). Simpulan penelitian ini ialah terdapat penurunan nilai NLR, PLR dan ferritin pada pasien Covid-19 setelah diberikan remdesivir terutama pasien hidup. Kata kunci: remdesivir; coronavirus disease 2019 (Covid-19); platelet lymphocyte ratio; neutrophil lymphocyte ratio; feritin